Konsep Dasar Pemahaman Algoritma Pemrograman - Halimatussya’diyah Purba; Yahfizham Yahfizham (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
When people hear the word algorithm, they definitely think it has something to do with programming languages, computer science, mathematics, and lots of numbers. This is true because algorithms are closely related to computer science. An algorithm is a certain series of logical steps to solve a problem. A collection or series of instructions designed to solve a problem is called a program. And writing a program in a programming language is called programming. Programming algorithms are the basic things you need to know and are the first step in the programming process. Algorithms can be presented in two ways, namely written or illustrated, following a method or following the programmer's steps. The purpose of writing this article is to find out basic concepts or initial understanding of programming algorithms. In this article the author uses a method, namely the literature study or library research method. The literature study method used is also accompanied by bibliometrics. The results of this research describe the characteristics, basic structure, functions, notation and examples of programming algorithms.